2020
DOI: 10.1136/bmjopen-2019-033532
|View full text |Cite
|
Sign up to set email alerts
|

Circulating liver enzymes and risks of chronic diseases and mortality in the prospective EPIC-Heidelberg case-cohort study

Abstract: ObjectivesElevated liver enzyme concentrations in blood are indicative of liver diseases and may provide an early signal for being at risk for other chronic diseases. Our study aimed to assess the relationships of alkaline phosphatase (ALP), gamma-glutamyltransferase (GGT), alanine aminotransferase (ALT), aspartate transaminase (AST) and the De Ritis ratio (AST/ALT) with incidence and mortality of cardiovascular diseases (CVD) and the four most common cancers, that is, breast, prostate, colorectal and lung.Set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
3
32
0
Order By: Relevance
“…An inverse association of ALT with risk of overall cancer 10 or mortality has been reported in prior studies 30,44,45 . The EPIC‐Heidelberg case‐cohort study, the only existing study that examined AST in relation to CRC risk, reported no associations 11 . However, the EPIC‐Heidelberg study had a small number of CRC (n = 256) and the participants had much higher levels of liver enzymes than ours, which may have explained the null findings, based on our observation that the inverse association between liver function markers and CRC weakened at the higher end of the biomarker levels.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…An inverse association of ALT with risk of overall cancer 10 or mortality has been reported in prior studies 30,44,45 . The EPIC‐Heidelberg case‐cohort study, the only existing study that examined AST in relation to CRC risk, reported no associations 11 . However, the EPIC‐Heidelberg study had a small number of CRC (n = 256) and the participants had much higher levels of liver enzymes than ours, which may have explained the null findings, based on our observation that the inverse association between liver function markers and CRC weakened at the higher end of the biomarker levels.…”
Section: Discussionmentioning
confidence: 75%
“…As for GGT, previous studies reported inconsistent but mostly positive associations with overall cancer risk, [11][12][13][14]46,47 and some also reported a positive association with CRC risk in men, 12 in current alcohol drinkers 13 and for colon cancer. 14 However, participants in those studies had much higher levels of GGT and most observed a higher disease risk in the highest category only.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The evaluation of liver enzymes in patients without liver diseases has become an emerging topic of research, most likely due to progressive aging of the population, increasing use of hepatotoxic drugs and better knowledge of non-alcoholic fatty liver disease [ 1 3 ]. Elevated liver enzymes in asymptomatic people has been associated with an increased risk for cardiovascular diseases or death, [ 4 8 ] and an increased incidence of venous thromboembolism (VTE) in one study [ 9 ]. Moreover, liver fibrosis is an important prognostic factor in patients with a number of liver disorders [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%